Petani dan Kemiskinan: Sekelumit Keluh Kesah dan Permasalahan Petani di Desa Mutunggeding - Gunawan, Fransiskus Xaverius Candra; Mesa, Asinkritus Ngongo Lalu Manu; Syah, Robby Firman; Simandjorang, Bonataon Maruli Timothy Vincent; Fitri, Suci Emilia (Jurnal Bina Praja, 2022)
Poverty reduction strategies should refer to who and why poverty occurs to make sustainable development programs effective for the welfare of society. The research aims to describe the problem conditions of the farmer households in Mutunggeding Village, Umalulu District, East Sumba Regency, with an overview of natural assets and human and physical resources. The research method used descriptive qualitative based on secondary and primary data from observations, documentation, and in-depth interviews with 102 randomly selected farmers to answer 41 key questions. The study results found that most farmers were young farmers with paddy fields and gardens, had low education and had supporting skills and good health. However, these land assets have yet to function optimally to meet household economic needs due to a scarcity of subsidized fertilizers, minimal hand tractors, and uneven distribution of irrigation water. This condition will be even more severe if the farmer must bear the burden of customs and culture, so you must go into debt and pawn your paddy fields. On the other hand, the strength of the community's social assets is a strong capital to survive against poverty. Therefore, the Government needs to strengthen the synergy of farmer groups, agricultural BP3K, and BUMDesa in overcoming the fundamental problems experienced by farmers and also needs to strengthen the institutional capacity of BUMDesa as a foundation for improving the people's economy.